Biochemical study of the effect of typhoid fever and brucellosis infections on some serum salts concentration - Amal, Al–Hadithi H. (Al Mustansiriyah Journal of Pharmaceutical Sciences, 2004)
Twenty cases of typhoid and brucellosis patients were studied on clinical, serological and biochemical aspects. The mean clinical findings were, most of the cases had sustained fever 66%, gastroenterial symptoms developed as the disease progressed and intestinal hemorrhage 19% as a complications. In serological findings, the number of patients who had +ve positive widal test were thirteen and those who had positive Rose Bengal test were five and those who had positive Widal and Rose Bengal test were two patients. The study was also conducted on ten apparently healthy individual as a control group. The objective : (1) To study the possible correlation between brucella infection and salmonella typhi infection by biochemical test of some serum salts, and (2) Because of the limited value of Widal’s test in the diagnosis of typhoid fever, serum salts of these patients studied to see if can be used as a recommended test to differentiate between these two diseases. The biochemical findings were reveled a significant increase in the level of serum magnesium (P0.004) and a significant decrease in the level of serum potassium (P0.003) in typhoid fever patients. While patients with brucellosis show moderate increase in the mean value of serum magnesium and sodium (P0.1 and P0.08 respectively) and moderate decrease in the mean value of serum potassium (P0.08).While patients with typhoid and brucellosis (combination) show significant increase in the mean value of serum magnesium and sodium (P0.001 and P0.001 respectively) while there is increased in the level of serum total calcium (P0.1) in patient with typhoid fever only. While serum ionized calcium show significant increase in the mean value in patients with typhoid fever and brucellosis (P0.06). The changes in these biochemical parameters were well discussed .